Original Intents: Individual Requirements for Candidates of Regional Representative Council - Ganiviantara Pratama (Constitutionale, 2020)
The main problem of this research is that there is no firmness regarding the diction of individual words in the Constitution which is useful as a condition for nominating Regional Representative Council or Dewan Perwakilan Daerah (DPD) membership. This indecisiveness has led to the composition of DPD membership being dominated by members of political parties. This journal aims to explore the meaning of the diction of words contained in the 1945 NRI Constitution, namely "Individual" which is clearly written in Article 22E paragraph (4) of the 1945 Constitution of the Republic of Indonesia after the Constitutional Court Decision No30/PUU-XVI/2018. The meaning of the term “individual” in this article will determine the conditions for nominating members of the DPD so that they are more in line with the objectives of establishing the institution. This journal uses a statutory approach and a historical approach. The results of this discussion show that the original intense definition concluded by the author regarding the word "individual" in the 1945 Constitution of the Republic of Indonesia after the Constitutional Court Decision has the following meaning: an individual who does not have a political party background or political party management and really understands his / her region.